2020
DOI: 10.3390/jcm9030792
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Specific TSH Upper-Limit Reference Intervals in the General French Population: There Is a Need to Adjust Our Actual Practices

Abstract: It is well known that thyroid dysfunction increases with age. This study is aimed to determine reference intervals, in males and females, suitable for thyroid disease exploration during adult life using routinely collected serum thyrotropin (TSH) data in a tertiary center from 2007 to 2018. Over 11 years, 295,775 TSH levels were measured in a single lab. Among the 156,025 TSH results available for analysis, 90,538 values were from female subjects, 82,019 were from patients aged >60 years and 26,825 were from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…This yielded a reference value for TSH from 0.62 to 6.86 mIU/L, which significantly lowers the percentage of individuals with subclinical hypothyroidism compared to our reference values. A study in France suggested the use of age-specific and sex-specific reference values for TSH, with upper-limit reference values >5.0 mIU/L for women over the age of 70 [39]. This might partly explain the large number of individuals with a normal FT4 in combination with a slightly elevated TSH in the current study.…”
Section: Plos Onementioning
confidence: 82%
“…This yielded a reference value for TSH from 0.62 to 6.86 mIU/L, which significantly lowers the percentage of individuals with subclinical hypothyroidism compared to our reference values. A study in France suggested the use of age-specific and sex-specific reference values for TSH, with upper-limit reference values >5.0 mIU/L for women over the age of 70 [39]. This might partly explain the large number of individuals with a normal FT4 in combination with a slightly elevated TSH in the current study.…”
Section: Plos Onementioning
confidence: 82%
“…Twenty-three articles were included, of which 7 articles contained a survey on both reference and disease-free populations. In addition, the TIDE study was also included in the present meta-analysis; thus, 31 studies were included (12,19,20,.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Specifically, the disease-free population includes subjects without reported thyroid disease, goiter, or use of treatments affecting thyroid function (2). Although the RI for TSH calculated based on the disease-free standard is not as accurate as the NACB standard, several large-scale studies based on this method have provided valuable information about the specific RIs for TSH in different regions (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…After reading the remaining 216 articles, 195 articles were excluded. Finally, the remaining 21 [4][5][6][7][8][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] studies were included in this meta-analysis (16 published in English and 5 in Chinese). The ow chart is as follows (Figure 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%